Antibody Response against SARS-CoV-2 Following ChAdOx1(Astezeneca AZD 1222) Vaccine in Health Care Workers in a Tertiary Care Hospital in India - Felice FAIZAL; Rajneesh JOSHI; R CHATTERJEE; Ankur AHUJA (Modern Medicine)
BACKGROUND: The ChAdOx1 nCoV-19 vaccine against COVID-19 is a two-dose vaccine spread 3 to 4 weeks apart. This study aims to ascertain the antibody response to each dose with respect to age, previous infection status etc. METHODS: Baseline total COVID-19 antibody level was ascertained using Siemens SARS-CoV-2 Total Antibody assay in consenting health care workers before the first dose of vaccination. Adverse effects were noted in each individual and were monitored weekly for the total antibody titre following both doses. Descriptive statistical tests were used to analyse the changes in antibodies levels weekly after both doses. Association of previous COVID infection and age with antibody levels was assessed. RESULTS: Median (range) of age of the 30 study participants was 31.5 years.23% of the participants had a history of previous COVID-19 infection. Mild adverse events following immunisation were reported by 87% participants after first dose whereas only in 7% after second dose. Median baseline antibody titres were significantly higher among those with previous COVID infection as compared to previously uninfected individuals. Antibody titres increased consistently after first dose and showed a declining trend following the second dose in all participants and showed no significant association with previous COVID-19 infection or age. CONCLUSIONS: Antibody titre response was similar amongst the various age groups. Higher response in the previously infected individuals following first dose may make them ideal candidates for a single dose vaccine regimen. Individuals showing lower levels of neutralising antibodies can be ideal candidates for a booster dose.